2019
DOI: 10.15381/anales.v80i1.15878
|View full text |Cite
|
Sign up to set email alerts
|

Estrategias para mejorar el acceso a medicamentos en el Perú

Abstract: El mercado de medicamentos en el Perú se ha duplicado en los últimos años; y está compuesto por un mercado público y un mercado privado. Medido en unidades de venta, el mercado público es el 70% del total y el mercado privado sólo el 30%. Pero medido en valor, esa proporción se invierte. El mercado público comprende tres sub-mercados diferentes: 1) medicamentos estratégicos que el Estado provee a toda la sociedad, como las vacunas y otros; 2) medicamentos no estratégicos, que son la mayoría de medicamentos que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…There is an increased need to develop DUR in Peru due to the increased demand for medications ( UgarteUbilluz, 2019 ). Currently, there is limited and incomplete information on drug use due to various factors, such as inadequate drug information, HCP with basic training on drugs, prescribing and dispensing activities influenced by socio-cultural patient demands and drug promotion, and the weakness of Peruvian drug policies ( Paredes et al, 1996 ; Maldonado et al, 2002 ; Bustamante Robles et al, 2012 ; Florián-Castro, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is an increased need to develop DUR in Peru due to the increased demand for medications ( UgarteUbilluz, 2019 ). Currently, there is limited and incomplete information on drug use due to various factors, such as inadequate drug information, HCP with basic training on drugs, prescribing and dispensing activities influenced by socio-cultural patient demands and drug promotion, and the weakness of Peruvian drug policies ( Paredes et al, 1996 ; Maldonado et al, 2002 ; Bustamante Robles et al, 2012 ; Florián-Castro, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results are a cause for concern when the public market for medicines represents 71% of the national market and where increasing access to generic medicines has been proposed as a strategy to improve access to medicines in Peru. ( 36 ) However, in spite of the possible mistrust, the annual evolution of generic prescription drug sales has demonstrated a progressive increase globally since 2010, and the strategies for their acceptance have been successful. ( 37 )…”
Section: Discussionmentioning
confidence: 99%
“…( 34 ) Some strategies for the first point have been suggested that include the programming and acquisition of strategic drugs in the Pan American Health Organization (PAHO) according to the prioritized population. ( 36 ) Likewise, strategies for financing according to programming, and coordination with regional governments and health institutions to ensure distribution and application throughout the sector. ( 36 ) Finally, strengthen execution monitoring mechanisms throughout the sector.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our study should be interpreted carefully because it represents to a special cohort without the barriers of access to drugs that is common in the Peruvian public system [ 18 ]. We observed some differences in 5-year survival rate in comparison to data of CONCORD-3 programme evaluating data from the Metropolitan Lima Cancer Registry.…”
Section: Discussionmentioning
confidence: 99%